Source-to-sink analysis of ancient sedimentary systems using a subsurface case study from the Møre-Trøndelag area of southern Norway: Part 2 – sediment dispersal and forcing mechanisms - Somme,TO; Jackson,CAL (Basin Research, 2013)
The composition, volume and stratigraphic organisation of submarine fan systems deposited along continental margins are expected to reflect the landscape from which the sediment was derived. During the Late Cretaceous, the Møre-Trøndelag margin, Norwegian North Sea was dominated by the deposition of deep-marine fines; the emplacement of 11 sand-rich submarine fan systems occurred only during a c. 3 Myr period in the Turonian-Coniacian. The systems were fed by sediment that was routed through submarine canyons incised into the basin margin; the canyons are underlain by angular unconformities and are interpreted to have resulted from tectonically-induced changes in slope physiography and erosion by gravity flows. The areal extent of the onshore drainage catchments that supplied sediment to the fans has been estimated based on scaling relationships derived from modern source-to-sink systems. The results of our study suggest that the Turonian fans were sourced by drainage catchments that were up to ~3600 km2, extending more than ~100 km inland from the palaeo-shoreline. The estimated inboard catchment extent correlates to the innermost structures of a large, long-lived, basement-involved, normal fault complex. Based on our analysis we conclude that increased sediment supply to the Turonian fan systems reflects tectonic rejuvenation of the landscape, rather than eustatic sea-level or climate fluctuations. The duration of fan deposition is thus interpreted to reflect the ‘relaxation time’ of the landscape following tectonic perturbation, and fan system retrogradation and abandonment is interpreted to reflect the eventual depletion of the onshore sediment source. We demonstrate that a better understanding of the stratigraphic variability of deepwater depositional systems can be gained by taking a complete source-to-sink view of ancient sediment dispersal systems.